Climate adaptation plans and “green jobs”: challenges for implementing a responsive, multi-skilled workforce in Worcester, Massachusetts - Varun Bhat; Sarah Strauss (Frontiers in Sociology)
Cities across the United States are affected by climate change impacts, and several cities have adopted climate adaptation plans to respond to this growing threat. These plans outline interventions that require a multi-skilled workforce working towards “green” or sustainable goals. However, the “green jobs” linked to these goals are ill-defined and misunderstood among employers and job seekers and can cause gaps in implementing the interventions outlined in the climate adaptation plans. Therefore, it is important to analyze the current state of green jobs in US cities and understand what employers, job seekers, and others think of the green jobs market. We conduct this analysis with the help of natural language processing and qualitative coding in the City of Worcester, Massachusetts, USA using job data from Indeed and semi-structured interviews. We find that the current green job market in Worcester is siloed around green jobs requiring degrees and that non-degree green jobs are significantly less present. Moreover, most green jobs are located far away from Worcester, making them unattractive to job seekers, influencing the overall image of green jobs among job seekers. Finally, both policymakers and employers are unclear about the definition of a “green job” impacting a job seeker’s search behaviors. All this points to a vague description of green jobs and green workforce, that can significantly impact Worcester’s ability to achieve a climate-ready workforce and to achieve its climate adaptation goals.